Development of A Management Guideline Wheel for Abnormal Pap Smears and Related Cervical Pathology - M Samy Ismail (Annals of Cytology and Pathology - Peertechz Publications, 2020)
A Management Guideline Wheel for Abnormal Cervical Pap Smears and related Cervical Pathology has been designed and developed to facilitate a standard and improve the quality of care in management of abnormal cervical cytology, precancerous lesions and cancerous lesions of the cervix. Each step of the wheel takes into account the context of the patient's medical condition, which include past medical/surgical history, patient compliance, patient awareness regarding the screening process, and the availability of treatment modalities for precancerous cervical lesions.  Management guidelines were revised by comparing existing guidelines on cervical cancer screening from the World Health Organization (WHO), the American guidelines, guidelines of the American College of Obstetricians and Gynecologists (ACOG), the United States Preventive Services Task Force (USPSTF), the American Cancer Society (ACS), the American Society for Colposcopy and Cervical Pathology (ASCCP), the American Society for Clinical Pathology (ASCP), the American College of Physicians (ACP) and the American Society for Colposcopy and Cervical Pathology, the guidelines from Singapore and Canada, the National Institute for Healthcare and Excellence (NICE) and National Health Service (NHS) of the UK.